2008
DOI: 10.1007/s00262-008-0522-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased migration of Langerhans cells in response to HPV16 E6 and E7 oncogene silencing: role of CCL20

Abstract: Human papillomavirus (HPV) infection, particularly type 16, is causally associated with cancer of the uterine cervix. The persistence or progression of cervical lesions suggests that viral antigens are not adequately presented to the immune system. This hypothesis is reinforced by the observation that most squamous intraepithelial lesions (SILs) show quantitative and functional alterations of Langerhans cells (LC). The infiltration of immature LC in the squamous epithelium is mainly controlled by Macrophage In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 42 publications
1
40
0
3
Order By: Relevance
“…These chemokines are involved in the recruitment and proliferation of DCs and NK cells and have been shown to be coordinately induced after murine cytomegalovirus infection (48). In particular, MIP-3␣ has been described to control the migration of skin DCs (9). Therefore, the upregulation of these chemokines may be involved in the observed increase of DCs in IFN-treated animals which may have a role in the protection of the animals against FMDV.…”
Section: Discussionmentioning
confidence: 99%
“…These chemokines are involved in the recruitment and proliferation of DCs and NK cells and have been shown to be coordinately induced after murine cytomegalovirus infection (48). In particular, MIP-3␣ has been described to control the migration of skin DCs (9). Therefore, the upregulation of these chemokines may be involved in the observed increase of DCs in IFN-treated animals which may have a role in the protection of the animals against FMDV.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations sug- gest that the uptake of these complexes via Fc␥R leads to maturation on DCs and cross-presentation of antigens, resulting in tumor immunity [21,22]. It has been demonstrated that SILs show quantitative and functional alterations in DCs [23][24][25]. We decided to study the association of FcGR3A V158F polymorphism in two cohorts of women, one with regressed or stable LSIL and the other with HSIL with the hypothesis that this polymorphism may promote different capabilities in DCs or other immune cells for recognition of antibody-antigen complexes, development of ADCC and apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…Articles focusing on the following were excluded: condylomata acuminate, abnormal cytology, vaccine titers, genotyping, HPV biology only in females, HPV head and neck cancers, basic viral infection, proctology, and herpes simplex virus. Table 1 Burk et al, 2009;Da Costa et al, 2002;Day & Schelhaas, 2014;Doorbar et al, 2006;Duncan et al, 2015;Guiguet et al, 2009;Hessol et al, 2009;Joyce et al, 1999;Kajitani et al, 2012;Machalek et al, 2012;Matthews et al, 2003;Middleton et al, 2003;Morshed et al, 2014;Munger et al, 2004;Pokomandy et al, 2011;Pyeon et al, 2009;Roden et al, 2001;Schiller et al, 2010;Stanley et al, 2012;Strickler et al, 2005;Uronis & Bendell, 2007 Use of HTS for drug discovery Basu et al, 2011;Buck et al, 2006;Huang et al, 2012;Kumar et al, 2011;Mahida et al, 2013;Marin et al, 2015;Thompson et al, 2010 Note. HPV = human papilloma virus; HTS = high-throughput screening techniques.…”
Section: Methodsmentioning
confidence: 96%
“…E6 and E7 are the primary oncogenes in HPV and together they are responsible for dysplastic changes at the cellular level and the progression to invasive cancer. E6 and E7 function by inactivating p53 and retinoblastoma protein (pRb; Matthews et al, 2003). The normal functions of p53 and pRb are to enable cells to maintain cell cycle DNA potential (Munger et al, 2004).…”
Section: Hpv Biology and Pathogenesismentioning
confidence: 99%